Beyond the Post-Industrial Park: the spatial heritage of Fundidora de Hierro y Acero de Monterrey glimpsed - Juan José Reyna Monrreal (Ciudades, 2018)
Though widely recognized for its post-industrial park, the urban heritage of Fundidora transcends the boundaries of its furnaces and needs to be addressed in the neighborhoods, schools, and infrastructure that the company planned, designed, built, and subsidized throughout the city. The 1950s district of Fraccionamiento Buenos Aires as well as the 1970s Fraccionamiento Adolfo Prieto are arguably some of the fi rst fully planned communities in the municipality, an exceptional trait particularly amongst the working-class districts of the time. As part of the city’s history, these two neighborhoods represent Fundidora’s contribution to the modernization of urbanism and architecture in Monterrey.